2008
DOI: 10.1007/s11062-009-9053-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Activity of Dopaminergic Neurons of the Ventral Tegmentum and Spectral Power of the EEG Rhythms in Awake Cats

Abstract: We studied correlations between the frequency of background impulse activity (BIA) of dopaminergic (DAergic) neurons of the ventral tegmentum (VT) and spectral power (SP) of the frequency components of EEG samples recorded in awake cats. The EEG was recorded monopolarly (electrodes were fixed in the cranial bones) from the frontal, occipital, and right and left temporal regions of the cortex. In a great majority of the cases, the BIA frequency of VT DA-ergic neurons demonstrated significant positive correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
(12 reference statements)
0
3
1
Order By: Relevance
“…This can be manifested in the pattern of current EEG as an increase in the SPD of the alpha rhythm. In our earlier studies on animals, we found a positive correlation between the levels of the activity of DA neurons of the VT with the SPD of the above-mentioned alpha EEG component [5]. At the same time, we found no significant correlations of spiking of the above neurons with the theta rhythm SPD.…”
Section: Resultscontrasting
confidence: 52%
See 2 more Smart Citations
“…This can be manifested in the pattern of current EEG as an increase in the SPD of the alpha rhythm. In our earlier studies on animals, we found a positive correlation between the levels of the activity of DA neurons of the VT with the SPD of the above-mentioned alpha EEG component [5]. At the same time, we found no significant correlations of spiking of the above neurons with the theta rhythm SPD.…”
Section: Resultscontrasting
confidence: 52%
“…From this aspect, the effects of such procedures on the aminergic cerebral systems deserve special attention. These systems, as is known, play a key role in the initiation and control of some crucially important behavioral phenomena, and the state of these systems specifically correlates with the characteristics of definite EEG rhythms [3][4][5]. In our earlier studies [5], we demonstrated in cats that the activity of dopaminergic (DA) neurons of the ventral tegmentum (VT) manifests significant positive correlation with the spectral power density (SPD) of the alpha EEG rhythm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, adaptive abilities of the CNS increase, and excessive levels of personal and situational anxiety decrease. As to the neural mechanisms of these effects, the results of studies of the interrelations between the EEG characteristics and the frequency of spiking of neurons localized in a few brainstem structures in cats allowed us to suppose the following [25]. Neurofeedback training directed toward an increase in the alpha rhythm SPD results in intensification of the activity of the cerebral dopaminergic system, in particular of its part localized in the ventral tegmentum.…”
Section: Resultsmentioning
confidence: 99%